DESIGN OF LAMP CONTROL LONG DISTANCE USING VIA BOT WHATSAPP BASED IOT NODEMCU - Kelvin; Nopriadi, Nopriadi (Computer Science and Industrial Engineering, 2023)
An electronic lamp is a lighting source for both inside and outside the house. One of the key components to carrying out daily tasks is the extensive use of lighting. Lights can be used for more than just illumination; they can also be utilized for décor, as a sign that the owner is at home, and to increase security. The Internet of Things (IoT), which is defined as a system of networks that may be connected to a machine or other object that serves as a receiver or sends data using a network connection, is essential for enabling the light control system and is the key to success in remote light control. The Internet of Things is another technology that necessitates a process and the cooperation of supporting hardware. Researchers will create a tool for controlling lights using Whatsapp as the media controller, NodeMCU as a support tool, Wifi as the internet network, and the Arduino IDE application as the controller in this study. As technology advances, so do the demands for lighting control, particularly in terms of energy savings and ease of monitoring. Based on this context, this study will employ Whatsapp as the media controller, as there is still very little light control found in Whatsapp, despite the fact that almost everyone, particularly in Indonesia, uses Whatsapp as a chat application. It is intended that the model device created by this researcher will be used to monitor lights as well as save electricity when the lights are not in use. This lamp controller is built with NodeMCU V3 CH340 and Relays that are linked together with Jumper Cables and other supporting components. This tool is created as part of an effort to advance technology and provide comfort and convenience in controlling lights. Based on the results of testing the designed equipment, the system built on the tool is capable and successful in controlling lights via Whatsapp by typing commands set in the Arduino IDE. The presence of a light control feature via Whatsapp will be a new breakthrough that anyone can use to save electricity and make it easier for lamp users to control lights remotely.